Self-reflective literary discourse in the Peruvian narrative tradition: the case of Historia secreta de una novela (1971) by Mario Vargas Llosa - Heredia Mimbela, Lenin (2020)
The purpose of this paper is to discuss the genesis or emergence, within the Peruvian literary system, of a self-reflective literary discourse whose aim is to present the writing process of a work from the point of view of its author. In order to clarify the features and strategies found in this particular type of discourse, we analyze the case of Historia secreta de una novela (1971) [The Secret History of a Novel], an essay by Mario Vargas Llosa. Finally, the main characteristics of this type of discourse are specified, such as the presence of a dialogical, autobiographical, prescriptive or testimonial component, at a micro-discourse level.